2017
DOI: 10.1080/10245332.2017.1396044
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements in children having transfusion-dependent beta thalassemia

Abstract: The study showed that children with beta thalassemia major had delayed physical growth possibly secondary to iron overload. Effective and early iron chelation is needed for preventing growth failure in transfusion-dependent beta thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
3
21
0
1
Order By: Relevance
“…This comes in accordance with Moiz et al [38] who found significant negative correlation between height for age z-score and serum ferritin levels and Rathaur et al [39] who found (65.71%) of studied patients had short stature, 77% were underweight and rest had normal BMI and they found also statistically significant negative correlation between serum ferritin and short stature .…”
Section: Discussionsupporting
confidence: 91%
“…This comes in accordance with Moiz et al [38] who found significant negative correlation between height for age z-score and serum ferritin levels and Rathaur et al [39] who found (65.71%) of studied patients had short stature, 77% were underweight and rest had normal BMI and they found also statistically significant negative correlation between serum ferritin and short stature .…”
Section: Discussionsupporting
confidence: 91%
“…Study setting and patient recruitment has been described previously [6]. Briefly, 367 diagnosed cases of transfusion dependent β-TM between 5 and 17 years of age were recruited from the outpatient clinics of a non-profit organization providing free of cost blood components to the patients with various chronic blood disorder.…”
Section: Methodsmentioning
confidence: 99%
“…In a cross sectional survey of patients with transfusion dependent β-TM, our group reported iron over load and delayed physical growth [6]. In addition, in the same group of patients altered bone and mineral homeostasis (as indicated by hypocalcemia, hyperphosphatemia, vitamin D deficiency and altered parathyroid hormone activity) was identified with high frequency of pain and fractures in 12.5% of patients (submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Patients with ß thalassemia commonly have skeletal abnormalities including limbs,vertebral column,skull and bones of the face, commonly called squirrel -like face [9] . Theorofacial bone changes are the results of ineffective erythropoiesis, the bones become thinner with pathological fractures may occur due to overexpansion of the bone marrow and extra medullary region and this is frequently noticed in patients who receive insufficient or irregular blood transfusions [10,11] . Patient survival depends on regular blood transfusions and iron chelating therapy,In spite of being an effective cure but there are many serious associated long-term problems.…”
Section: Introductionmentioning
confidence: 99%